Community involvement and sustainable rural tourism development: Perspectives from the local communities - Fong, Sook-Fun; Lo, May-Chiun (International University College, 2015)
The aim of this study is to examine the relationship between local communities’ involvement and sustainable rural tourism development in the existing tourism industry in Kuching namely, Kampung Annah Rais and Kampung Darul Islam Belimbing. In tourism industry, the way how tourism stakeholders are pleased with mass tourism have been deeply affecting the achievement of sustainable rural tourism development. A questionnaire survey was carried out among the local communities who are currently staying and have been staying in these rural tourism destinations for more than a year. A sample of 113 usable questionnaires was obtained. Four hypotheses were developed regarding the effects of participation in decision making, knowledge sharing, empowerment, and community knowledge about tourism on social, cultural, economic, and environmental sustainability. The findings suggest that local communities’ participation in decision making, empowerment, and community knowledge about tourism do affect the sustainability of rural tourism development. Interestingly, findings indicated that knowledge sharing does not show positive relationship on sustainable rural tourism development. It is believed that poor relationship among the tourism stakeholders influences the effectiveness of knowledge sharing. Suggestions for practical implications and future research are discussed further. © 2015 Varna University of Management.